The Effects of Terminalia catappa L. Leaves Extract on the Water Quality Properties, Survival and Blood Profile of Ornamental fish (Betta sp) Cultured - Nugroho, Rudy Agung; Manurung, Hetty; Saraswati, Dewi; Ladyescha, Deasy; Nur, Firman Muhammad (Biosaintifika: Journal of Biology & Biology Education, 2016)
This research aimed to determine the phytochemicals content of Terminalia catappa leaves extract (TCL) and its effects on the survival and blood profiles of ornamental fish (Betta sp) Ninety fish were randomly assigned into six triplicates groups and reared in various concentration of TCL: 0 (control), 125, 250, 375, 500, 625 ppm for 30 days. Temperature, Dissolve oxygen (DO), and pH were monitored during the trial. After 30 days, survival, Red Blood Cells (RBC), White Blood Cells (WBC), haemoglobin (Hb), lymphocyte, and total protein serum (TPS) were analyzed. Based on the phytochemicals test, saponin, triterpenoid, quinon, phenolic, tannin, and flavonoid were detected on the TCL. Temperature and DO were not affected by any concentration of TCL. The lowest pH (5.05) was found in fish medium immersed with 625 ppm of TCL. Adding TCL above 375 ppm resulted in significantly higher survival, RBC, and Hb. The highest WBC was found in fish immersed with 625 ppm whereas the lowest lymphocyte was found in fish immersed with 375 of TCL. However, immersing any various concentration of TCL did not affect on the TPS. In summary, immersing TCL above 375 ppm is beneficial to enhance survival, RBC, WBC, and Hb of Betta sp.How to CiteNugroho, R. A., Manurung, H., Saraswati, D., Ladyescha, D. & Nur, F. M. (2016). The Effects of Terminalia catappa L. Leaves Extract on the Water Quality Properties, Survival and Blood Profile of Ornamental fish (Betta sp) Cultured. Biosaintifika: Journal of Biology & Biology Education, 8(2), 240-247.